2022
DOI: 10.3390/nu14122407
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Food Insecurity among Pregnant Women and Caregivers of Children Aged 0–6 Years: A Scoping Review

Abstract: With a global focus on improving maternal and child nutrition through the 2030 Sustainable Development Goals, it is important to understand food insecurity in pregnant women and families with young children, as food insecurity at these life stages can have ongoing negative health consequences. However, factors that influence food insecurity among this population group are not well understood. This scoping review investigates the factors that influence food insecurity among pregnant women and households with yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…Of the 449 surveys that were attempted, 66 were excluded as the respondent did not consent to the study or no questions were answered, 29 were excluded as they were currently not pregnant, 51 respondents were excluded as they did not answer one or more questions about food insecurity, leaving 303 participants with complete data who have been included in the analysis. For details on the sample and the factors that may contribute to food insecurity in this population please see [ 30 , 31 ]. Food insecurity was estimated using the single item and the 2-item, 6-item, and 10-item versions of the HFSSM, with the levels of food insecurity 6.2%, 11.4%, 11.7% and 14.3%, respectively, (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 449 surveys that were attempted, 66 were excluded as the respondent did not consent to the study or no questions were answered, 29 were excluded as they were currently not pregnant, 51 respondents were excluded as they did not answer one or more questions about food insecurity, leaving 303 participants with complete data who have been included in the analysis. For details on the sample and the factors that may contribute to food insecurity in this population please see [ 30 , 31 ]. Food insecurity was estimated using the single item and the 2-item, 6-item, and 10-item versions of the HFSSM, with the levels of food insecurity 6.2%, 11.4%, 11.7% and 14.3%, respectively, (see Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The full details of the scoping literature review and qualitative interviews have been published elsewhere (References [ 15 , 16 ]). In brief, findings from the qualitative interviews identified a range of prominent themes associated with food insecurity.…”
Section: Resultsmentioning
confidence: 99%
“…The study was designed and has been reported in accordance with the COREQ checklist for qualitative studies [ 14 ]. The first two stages of this study are summarized below and have been published with full details available [ 15 , 16 ] with the next three stages reported in full detail for the first time below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations